Developing the ethical foundations of Islamic economics: benefitting from Toshihiko Izutsu - Haneef, Mohamed Aslam; Furqani, Hafas (IIUM Press, 2009)
Toshihiko Izutsu (1914-1993) is among the few 20th Century scholars who attempt to derive ethical principles of Islam from the Qur´Én by applying semantic analysis of Qur´Énic terms/concepts. Can his approach contribute to the development of an Islamic science in general, and of Islamic economics in particular, especially in the endeavour to establish the ethical principles of Islamic economics? In this paper, we scrutinise Izutsu’s two works on God and Man in the Qur´an (2002) and Ethico-Religious Concepts in the Qur´an (2004 to derive relevant Islamic values from the Qur´Én that could form the ethical base of Islamic economic theories as well as policy prescriptions. In particular, the concept of man as khalÊfah-Ñabd is seen as having significant ethical implications on how economics and economic decision-making would be developed.